Culture and neural frames of cognition and communication - Han, Shihui; Pöppel, Ernst; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
Cultural neuroscience combines brain imaging techniques such as functional magnetic resonance imaging and event-related brain potentials with methods of social and cultural psychology to investigate whether and how cultures influence the neural mechanisms of perception, attention, emotion, social cognition, and other human cognitive processes. The findings of cultural neuroscience studies improve our understanding of the relation between human brain function and sociocultural contexts and help to reframe the ?big question? of nature versus nurture. This book is organized so that two chapters provide general views of the relation between biological evolution, cultural evolution and recent cultural neuroscience studies, while other chapters focus on several aspects of human cognition that have been shown to be strongly influenced by sociocultural factors such as self-concept representation, language processes, emotion, time perception, and decision-making. The main goal of this work is to address how thinking actually takes place and how the underlying neural mechanisms are affected by culture and identity.
Neuroplasticity: Biological Evolution/s Contribution to Cultural Evolution -- Cultural Neuroscience of Social Cognition --  The Brain and Its Self: Concepts of Self and the Cortical Midline Structures --  Self Identity in Sociocultural Contexts: Implications from Studies of Self-face Recognition --  The Relation Between the Self and Others: A Transcultural Neuroimaging Approach -- Unconscious Self-processing: Subconscious, Unintentional or Subliminal? -- Brain, Behavior, and Culture: Insights from Cognition, Perception, and Emotion --  Psychological Time, Time Perspective, Culture and Conflict Resolution --  Co-creation Systems: Ma and Communication --  Hearing Loss and Auditory Processing Disorders: Clinical and Experimental Perspectives --  Broca?s Area: Linking Perception and Production in Language and Actions --  Language Attrition and Identity -- The Logic of Constellations: A Complementary Mode of Thinking that is Crucial for Understanding How Reality  Actually Takes Place -- Three Modes of Knowledge as Basis for Intercultural Cognition and Communication: A Theoretical Perspective --  Two Modes of Thinking: Evidence from Cross-Cultural Psychology -- Outcome Evaluation in Decision Making: ERP Studies --  Mindfulness in Leadership: Does Being Mindful Enhance Leaders? Business Success?.
Electronic reproduction.
Keywords: Social perception; Cognitive neuroscience; Cognition -- Physiology; Neuropsychology; Brain -- Physiology; Cross-cultural comparison; Cultural characteristics; Social perception; Electronic books